Accurate detection of β-hCG in women's serum and cervical secretions for predicting early pregnancy viability based on time-resolved luminescent lanthanide nanoprobes. Issue 12 (12th March 2020) - Cai, Liangzhi; Huang, Yunmei; Sun, Pengming; Zheng, Wei; Zhou, Shanyong; Huang, Ping; Wei, Jiaojiao; Tu, Datao; Chen, Xueyuan; Liang, Zhiqing
Abstract : A strategy based on a LiLuF4 :Ce, Tb time-resolved photoluminescence nanoprobe was developed for β-hCG detection in women's serum and cervical secretions for predicting early pregnancy viability. Abstract : Sensitive and specific detection of β-hCG in women's serum and cervical secretions is of great significance for early pregnancy evaluation. However, the accurate detection of trace amounts of β-hCG in cervical secretions remains challenging because of its low level. Herein, we report a unique strategy for β-hCG detection in a heterogeneous sandwich-type bioassay by using LiLuF4 :Ce, Tb nanoparticles as time-resolved photoluminescence (PL) nanoprobes. By taking advantage of the intense and long-lived PL of the nanoprobes, the short-lived background autofluorescence can be completely eliminated, which enables the sensitive detection of β-hCG with a linear range of 0–10 ng mL −1 and a detection limit down to 6.1 pg mL −1, approximately two orders of magnitude improvement relative to that of a commercial β-hCG assay kit. Furthermore, we demonstrate the application of the nanoprobes for accurate detection of β-hCG in clinical serum and cervical secretion samples and unveil that the ratio of β-hCG levels in cervical secretions and serum can be a good indicator of early pregnancy viability in unknown locations. These findings bring new opportunities in perinatal medicine by employing luminescent lanthanide nanoprobes, thus laying a foundation for future development of luminescent nanoprobes for versatile biomedical applications.